Synthesis and Characterization of Magnetic Molecularly Imprinted Polymer for the Monitoring of Amoxicillin in Real Samples Using the Chromatographic Method - Rosario López; Sabir Khan; Sergio Espinoza Torres; Ademar Wong; Maria D. P. T. Sotomayor; Gino Picasso (Magnetochemistry, 2023)
Amoxicillin (AMX) is an antibiotic frequently used for the treatment of bacterial disorders and respiratory problems in both humans and animals. This work aims to synthesize a molecularly imprinted superparamagnetic polymer (SP-MIP) with a core-shell structure for the selective detection of AMX in real samples. Magnetite superparamagnetic nanoparticles (SNP) were prepared by the polyol method, coated with silica, and functionalized with silane groups. The polymerization process was executed using the free-radical precipitation method. Thermogravimetric analysis (TGA) was used to evaluate the thermal stability of the synthesized materials. The results obtained from N2 adsorption and desorption analyses showed that the surface area of SP-MIP (19.8 m2/g) was higher than that of the non-molecularly imprinted superparamagnetic polymer (SP-NIP—9.24 m2/g). The optimized adsorption analysis showed that both SP-MIP and SP-NIP followed SIP-type behavior, with adsorption constant KS 0.01176, 1/n 1.73. The selectivity tests showed that SP-MIP is highly selective for AMX in the presence of other molecules. Finally, for the recovery analysis, the application of SP-MIP for determining AMX in samples of tap water, river water, and drugs using HPLC yielded a mean recovery value of 94.3%.